Pengaruh Pengalaman Kerja Dan Tipe Kepribadian Terhadap Kinerja Karyawan (Studi SDM Pada: PT. Telkom Witel Sukabumi) - Rifera Cita Adeba; Faizal Mulia Z; Kokom Komariah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the description of work experience and personality type on employee performance, determine the effect of work experience on employee performance and determine the effect of personality type on employee performance. The method used in this research is descriptive and associative method with a quantitative approach, and distributing questionnaires to 31 respondents, namely employees of PT. Telkom Witel Sukabumi. The data analysis technique used by the researcher is regression analysis with the help of SPSS 24 software. The sampling technique used is the saturated sample or census technique, which means that all members are sampled, namely employees at PT. Telkom Witel Sukabumi, totaling 31 people. The results of this study indicate that work experience has no positive and significant effect on employee performance. While Personality Type has a positive and significant effect on employee performance. Keywords: work experience, personality type, employee performance